Choroidal changes and associations with visual acuity in diabetic patients - João Heitor Marques; Ana Marta; Catarina Castro; Pedro Manuel Baptista; Diana José; Daniel Almeida; António Ribeiro; Irene Barbosa (International Journal of Retina and Vitreous, 2022)
Abstract Background The variable visual function observed in diabetic retinopathy (DR) patients is not fully explained by the classic staging system. Our purpose was to evaluate choroidal changes, in standardized sectors, in DR patients and to find associations between choroidal measurements and visual function. Methods Cross-sectional study that included the right eye of diabetic patients (n = 265) without active edema, ischemia or neovascularization and age-matched controls (n = 73). Optical coherence tomography (OCT) imaging was performed with enhanced depth imaging protocol. Choroidal vascularity index (CVI) was calculated in a 5 mm scan centered in the fovea. Results CVI decreased with age (p < 0.001) but was not influenced by axial length. A multivariate analysis adjusting for age confirmed a significant difference in CVI between DR eyes that had previous treatments (intravitreal injections and/or photocoagulation) compared to control eyes (p = 0.013) and to DR eyes that never required treatment (p = 0.002). There was no significant difference between non-DR diabetic patients and normal controls. Considering the group of DR patients that had previous treatments, in eyes without optic media opacification, BCVA correlated with CVI (r = − 0.362, p < 0.001), whereas full retina thickness and individual retinal layer thickness did not (p > 0.066). Conclusions A reduction in CVI was observed in patients with a more advanced stage of DR. In treated DR patients with stable disease, choroidal biomarkers correlated with best-corrected visual acuity whereas retinal biomarkers did not. Trial registration: N/A